2019
DOI: 10.48084/etasr.2499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-Cement Ratio on Flexural Strength of RC Beams Made with Partial Replacement of Coarse Aggregates with Coarse Aggregates from Old Concrete

Abstract: This research paper presents an experimental evaluation of the effect of water-cement ratio on the flexural strength of reinforced concrete beams made with 50% replacement of coarse aggregates with recycled concrete aggregates (RCA). 72 reinforced concrete beams were cast using 0.54, 0.6, 0.65 and 0.70 water-cement ratio. In each ratio, 12 beams were cast using RCA and 3 beams were cast using all-natural coarse aggregates (NCA). Beams were cured for 7 and 28 days. After curing, all beams were tested with centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
2
8
1
Order By: Relevance
“…Cracking pattern and deflection response of beams containing waste aggregate are similar to those of natural aggregate concrete beams as reported by Malešev et al 2010 [14]; Seara-Paz et al 2018 [18]; Wang et al 2019 [21]; Oad et al 2019 [4]. However, some researchers indicated that deflection is greater and cracks are more and closer in waste aggregate beams due to lower modulus of elasticity and higher shrinkage, respectively [5,11,12,17,19].…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Cracking pattern and deflection response of beams containing waste aggregate are similar to those of natural aggregate concrete beams as reported by Malešev et al 2010 [14]; Seara-Paz et al 2018 [18]; Wang et al 2019 [21]; Oad et al 2019 [4]. However, some researchers indicated that deflection is greater and cracks are more and closer in waste aggregate beams due to lower modulus of elasticity and higher shrinkage, respectively [5,11,12,17,19].…”
supporting
confidence: 74%
“…On the other hand, demolition waste is increasing and has become one of the most serious concerns worldwide [1][2][3]. So, recycling waste materials in constructions offers environmental as well as economic benefits such as reducing extraction of virgin materials and overall projects costs [2,[4][5][6].Since concrete is the most common construction material and about 75 % of concrete volume is occupied by aggregate, waste materials like crushed concrete and/or crushed bricks have successfully used as coarse and/or fine aggregate in various percentages to produce new concretes even though they, generally; give lower strength and stiffness than conventional concrete [7][8][9][10][11][12]. However, studies show that less or no negative effect is observed when the ratio of waste aggregate is about 50 % or less [1,8,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…al. [13] used recycled coarse aggregate from demolish waste as replacement of conventional aggregates up to 100% replacement level. Based on the laboratory investigations of compressive strength of concrete cylinders, the authors concluded 50% replacement as optimum because the loss of compressive strength was least at this level of replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Unavailability of such spaces forces the industry to transport waste too far leading to increase the cost of the project, while dumbing it in nearby unsuitable areas may cause environmental issues. The conventional ingredients of concrete are believed to be no eco-friendly materials due to the processes involved in their production [2]. Therefore, Recycled Aggregate Concrete (RAC) is one of the solutions in dealing with waste on site and helping to minimize the associated issues to some extent.…”
Section: Introductionmentioning
confidence: 99%